English inversion : a ground-before-figure construction - Chen, Rong, 1955- (Cognitive linguistics research, 2003)
The book provides an account of English inversion, a construction that displays perplexing idiosyncrasies at the level of semantics, phonology, syntax, and pragmatics. Basing his central argument on the claim that inversion is a linguistic representation of a Ground-before-Figure model, the author develops an elegant solution to a hitherto unsolved multidimensional linguistic puzzle and, in the process, supports the theoretical position that a cognitive approach best suits the multidimensionality of language itself. Engagingly written, the book will appeal to linguists of all persuasions and to any reader curious about the relationship between language and cognition.